PERSEPSI ANGGOTA TERHADAP KINERJA PENGURUS DAN KAITANNYA DENGAN PARTISIPASI ANGGOTA PADA KUD KARYA SAWIT KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Kasdianti, Yesi; Suarman, Suarman; hardisem, hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This research aims to determine the influence of member perception on association performance toward member participation. This research was conducted at KUD Karya Sawit Kecamatan Rumbio Jaya Kampar District with 77 research samples obtained by using simple random sampling method. The data used are primary data and secondary data with data collection methods using questionnaires and documentation. Data analysis techniques used are Descriptive Analysis and Linear Regression Analysis processed through SPSS 24.0 Program. The results of this research reveal there is significant influence on member perception on association performance toward member participation. This means that if the association performance is better to members and the cooperative have a better member’s participation. Thus, to achieve a good level of cooperative member participation required support from association performance.Key Words : Association Performance, Member Perception, Member Participation